Drug Abuse Awareness Among Adolescent Of Low Social Economic Status - Vickgneshwari A/P Kanagaveloo; Zuriani Binti Zulkifli; Mohd Arief Sadik; Mohd Zulhusni Amirolmukminin (2024)
This study investigating the “Drug Abuse awareness among Adolescent of low social economic status”. The objective of this study is to measure the awareness of the use of drug substances and to measures the stress among the adolescents in low social economic status. The sample consisted of 91 respondents who have low social economic status. During survey there were two instruments were undertaken Alcohol and other drug abuse (AOD) and Depression anxiety stress scale (DASS) to measure the perception of the participants on the drug abuse and stress management. The findings indicates that the drug abuses among adolescent was reflection from the influential of low social economic status problem that make the adolescent addicted seriously to drug abuse it and they expressed that “it’s hard to relief from it”.